An Analysis of Learning Theory and Its Implementation in Islamic Religious Education Learning - Sultan, Sultan; Paewai, Rusman; Damayanti, Ina (International Journal on Advanced Science, Education, and Religion, 2025)
The aim of this research is to identify and analyze in depth the paradigm of theory and learning and provide an explanation of the types of learning theories in Islamic religious education. The method used to analyze data is library research, namely collecting various references from sources relevant to the object of study. The results of this research show that theory in learning is an instrument that has been tested for truth and is studied from various different perspectives, while learning is a process of changing human behavior based on experience and training to become knowledgeable. Several theories that researchers have formulated include: fitrah theory, connectionism theory, power psychology theory, and gestalt theory.